Sweron as a Model for Integral Ecological Education in Papua: a Contextual Theological Study - Yulko, Yulianus Korain; Bame, Athanasius; Wijanarko, Robertus (Journal of Asian Orientation in Theology, 2026)
This study examines Sweron as a model of integral ecological education in Papua: a contextual theological study. Sweron is a tradition of local wisdom passed down from generation to generation by the Papuan people, especially the Maybrat tribe, which functions as an ecological, social and spiritual mechanism in maintaining a harmonious relationship between humans, nature and God. This study aims to analyse the theological meaning of Sweron and its relevance as a model of integral ecological education amid the global ecological crisis. This study uses Gadamer's hermeneutic phenomenology method. Gadamer emphasises that hermeneutics is not merely a method for interpreting texts, but rather a philosophy of understanding rooted in dialogue between the interpreter and the interpreted reality. Understanding occurs through a process of fusion of horizons, namely the horizon of the researcher and the horizon of the text/subject. Data was collected through in-depth interviews, participatory observation, document study, documentation, and focused discussions with the community, traditional leaders, and those with a sufficient understanding of Sweron.Data analysis was carried out by combining three main frameworks: first, contextual theology, which views Sweron as a locus theologicus; second, Laudato Si' integral ecology, which emphasises the interconnectedness of the ecological, social, and spiritual dimensions; third, religion-nature-culture, which interprets Sweron as a form of ecological spirituality. The results of the study show that Sweron not only functions as a tradition-based environmental management system, but also contains theological values that affirm humanity's moral responsibility towards nature as God's creation. Sweron represents a model of integral ecology education that is holistic, contextual, and transformative, as a form of respect for nature that needs to be studied ecotheologically. This research contributes to the development of Sweron-based eco-theology by offering a new perspective for the Indonesian eco-theological discourse and enriching the dialogue between ecology, theology and culture in a sustainable manner.